2010
DOI: 10.1001/archsurg.2010.243
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Invasive Breast Cancer When Core Needle Biopsy Shows Ductal Carcinoma In Situ

Abstract: The risk of upstaging can be estimated by using preoperative features in patients with DCIS on CNB. We propose a management algorithm that includes sentinel node biopsy for patients with DCIS who have microinvasion on CNB, palpable DCIS, 2 or more predictive factors, and planned total mastectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
43
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 52 publications
14
43
1
Order By: Relevance
“…Although the management of DCIS with microinvasion remains controversial, sentinel lymph node biopsy is usually recommended. 9 No mammographic features were associated with upstaging in the present study, a fi nding similar to that of previous studies. 10,11 The present study found no correlation between the size of the lesion, as seen by US or mammography, and upstaging.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although the management of DCIS with microinvasion remains controversial, sentinel lymph node biopsy is usually recommended. 9 No mammographic features were associated with upstaging in the present study, a fi nding similar to that of previous studies. 10,11 The present study found no correlation between the size of the lesion, as seen by US or mammography, and upstaging.…”
Section: Discussionsupporting
confidence: 93%
“…A preoperative diagnosis of invasive breast carcinoma associated with DCIS is important because routine axillary lymph node dissection is not recommended for the treatment of DCIS. 4,[8][9][10] Accurate preoperative diagnosis provides the opportunity for the patient to undergo a single-stage, more appropriate operation if invasive disease is identifi ed on CNB or is predicted to exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the situation where there are extensive calcifications and a core showing DCIS, excision will have cosmetic consequences, but without excising, the tumor you will not be able to confirm that 100 % of the calcifications represent DCIS. A non-surgical approach runs the risk of leaving invasive cancer untreated [22].…”
Section: Should a Mastectomy Ever Be Done For Dcis?mentioning
confidence: 99%